Potential of Discriminative Sensing of Strain and Temperature Using Perfluorinated Polymer FBG - Ishikawa, Ryo; Nakamura, Kentaro; Lee, Heeyoung; Kalli, Kyriacos; Mizuno, Yosuke; Theodosiou, Antreas (My University, 2019)
Though the strain characteristics of fiber Bragg gratings (FBGs) inscribed in perfluorinated graded-index (PFGI) polymer optical fibers (POFs) have been reported, their temperature characteristics have not yet been detailed. In this paper, we experimentally investigate the temperature dependence of the Bragg wavelength of a PFGI-POF-FBG. With the increasing temperature, each peak of the FBG-reflected spectrum shifted to longer wavelength with different coefficients. The temperature coefficient of one of the clearest peaks was 0.09 nm/°C, which was eight times larger than those of FBGs in silica single-mode fibers and almost the same as those of FBGs in polymethyl methacrylate POFs. A temperature-independent but strain-dependent peak was also observed, which indicates the potential of discriminative sensing of strain and temperature.
Keywords: Fiber Bragg gratings; Strain sensing; Polymer optical fibers; temperature sensing